Pengaruh Mengonsumsi Konten TikTok @Dailyjour Terhadap Pengetahuan Ilmu Parenting pada Pasangan Pernikahan Muda - Aprilyaningrum, Vina; Anita Agustina Wulandari (DIGICOM : Jurnal Komunikasi dan Media, 2024)
This research aims to determine the influence level of TikTok content @dailyjour on parenting knowledge among young married couples. The theory used is the S.O.R (Stimulus, Organism, Response) Theory, which relates to communication messages and reactions. The research method employed is quantitative, using questionnaires for data collection and conclusion drawing. The sampling technique used in this research is purposive sampling. Based on the conducted research, it can be concluded that the TikTok content @dailyjour has a significant influence on parenting knowledge among young married couples. The communicants are able to receive and process the stimulus from the TikTok content @dailyjour, resulting in an attitude change, specifically an increase in parenting knowledge.